KEUNTUNGAN PENERAPAN APLIKASI PROJECT MANAGEMENT TOOLS DALAM ORGANISASI BERBASIS TEKNOLOGI INFORMASI. STUDI KASUS IMPLEMENTASI REDMINE PADA PT MTI - Mantik, Hari Bagus P. (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2020)
This paper does not focus on project management, project manager tasks and so on. But how can stakeholders guard a project properly, correctly and effectively? The answer is to use project management tools. One project goes through several stages, each stage having its own duties, authorities, responsibilities and deadlines. The larger the size of the project, the more complex the lines of coordination, communication and collaboration that must be bound together. The use of project management tools, in this case the PT MTI case study using "RedMine software", is expected to reduce obstacles in communication, coordination and facilitate project completion according to agreed deadlines.Â Key words: project management tools, RedMine software